Prevalensi Kejadian Penyakit Tidak Menular (PTM) - Rusmini Rusmini; Hesti Kurniasih; Anita Widiastuti (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the characteristics of Posbindu participants and the incidence of non-communicable diseases. The research method used in this research is descriptive observational. The results showed that most (58%) found high blood pressure/hypertension, the majority (97.3%) found no high or regular blood sugar, on examination of uric acid, some (57.3%) found no high or normal uric acid as much Of the 63 people for cholesterol examination, the majority (85.5%) found normal cholesterol levels as many as 94 people. In conclusion, there is no significant relationship between gender and the incidence of hypertension, diabetes, gout, and high cholesterol. However, the analysis results show that women are more at risk for developing non-communicable diseases such as hypertension, diabetes, gout, and high cholesterol. Keywords: Early Detection, Climacterium, Elderly, Non-Communicable Diseases